2020
DOI: 10.11604/pamj.2020.36.311.19102
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices among Brazzaville midwives on cervical cancer screening

Abstract: Introduction cervical cancer is an illness that causes 250,000 deaths worldwide. Data on Health professional's skills is highly important for the elaboration of prevention strategies. Objective: assess the knowledge, attitudes and practices (KAP) among Brazzaville midwives on cervical cancer screening. Methods analytical KAP Study, from May 2 nd to August 10 th 2018. Participants are midwives working in the Gynaecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Studies ( 42 ) have also found an association between knowledge and attitudes. Moreover, since the classification of medical and financial resources existed in different regions, lack of knowledge has become a common problem that makes it harder for primary care physicians to provide CCSSs ( 43 ). Subsequently, we added the knowledge level to the research model, which may have a potential effect on primary care physicians' BI and PBC of providing CCSSs, and the following hypotheses were posited:…”
Section: Research Model and Hypothesis Developmentmentioning
confidence: 99%
“…Studies ( 42 ) have also found an association between knowledge and attitudes. Moreover, since the classification of medical and financial resources existed in different regions, lack of knowledge has become a common problem that makes it harder for primary care physicians to provide CCSSs ( 43 ). Subsequently, we added the knowledge level to the research model, which may have a potential effect on primary care physicians' BI and PBC of providing CCSSs, and the following hypotheses were posited:…”
Section: Research Model and Hypothesis Developmentmentioning
confidence: 99%